(untitled) (Al-Academy, 2018)
The design studies, especially in their contemporary stages, have not been isolated from the subjects that underpin advanced ideas in the field of technical treatments that enrich and improve the social life of users through those technological innovations that have enhanced and changed life styles, Especially in the field of general institutional techniques, including cinemas, as the ideal places for people and visitors to this space, which can contribute to the promotion of cultural, social and technical aspects within this millennium. DONC as reflected on the positive communication and communication between the intellectual and cognitive develop individuals, including cultural and technical side of the individual. The first chapter consisted of a methodological framework for research on the problem, importance, purpose and definition of terms. The second chapter included theoretical framework for research. The third chapter deals with the research methodology, description and analysis of the models, reaching conclusions, recommendations and finally the list of sources